2017
DOI: 10.1055/s-0037-1604331
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Extension of Tumor is as Important as Tumor Size to Facial Nerve Outcome and Extent of Resection for Vestibular Schwannomas

Abstract: We examined vestibular schwannoma tumor dimension and direction of growth to determine whether these correlate with facial nerve outcome as well as extent of resection (EOR). Retrospective review of prospectively maintained databases. 206 patients were a part of this study. Tumor dimensions were measured using preoperative magnetic resonance imaging, and a series of ratios were then calculated to further characterize tumor dimension. Regression analyses were performed to investigate correlation with facial ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
1
10
1
Order By: Relevance
“…Additionally, in a retrospective study of 206 VS-66% underwent RS resection and 34% underwent TL resection, Wong et al found that anterior extension, specifically greater than 15 mm of anterior extension, was associated with worse outcomes. 20 No VS in our sample had greater than 15 mm of anterior extension, so potentially the present study had a disproportionate number of more posterior positioned tumors. However, unlike the current study, Sharma et al, and Gerganov et al studies, Wong et al measured anterior extension from a line that bisected the internal auditory canal rather than from the anterior border of the internal auditory canal, making comparison more challenging.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, in a retrospective study of 206 VS-66% underwent RS resection and 34% underwent TL resection, Wong et al found that anterior extension, specifically greater than 15 mm of anterior extension, was associated with worse outcomes. 20 No VS in our sample had greater than 15 mm of anterior extension, so potentially the present study had a disproportionate number of more posterior positioned tumors. However, unlike the current study, Sharma et al, and Gerganov et al studies, Wong et al measured anterior extension from a line that bisected the internal auditory canal rather than from the anterior border of the internal auditory canal, making comparison more challenging.…”
Section: Discussionmentioning
confidence: 80%
“…One risk is that of facial paralysis, a potentially devastating outcome that has been demonstrated to result in psychological distress 1 and decreased quality of life (QOL) 2 . The risk of facial paralysis following surgical resection has been correlated with previous radiation therapy, increasing tumor size, 3–6 tumor position, 7 and direction of tumor growth 7–10 . With increasing tumor size, the facial nerve can become displaced, compressed, splayed across, or adherent to the surface of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…[10] In addition, a number of studies have been conducted to determine the pre-surgical factors to predict facial nerve results in schwannoma surgery. Wong et al [27] reported that factors such as advanced patient age, large dimensions of tumor and position according to surrounding anatomical structures (adhesion, compression, wrapping of normal structures by tumor tissue, etc. ), cystic or solid tumor character, surgical access route and increasing extent of surgical resection are factors affecting the prognosis negatively.…”
Section: Discussionmentioning
confidence: 99%
“…Images should be well examined before surgery in order to reveal the facial nerve-tumor relationship, the stiffness of the tumor, and selection of optimal surgical approach. [27] The success of surgery depends on the complete removal of the tumor without additional neurological deficits. Samii and Matthies's [37,38] study of 1,000 cases achieved a total resection rate of 97.9%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation